ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SMP TERHADAP KONSEP PENCEMARAN LINGKUNGAN DITINJAU DARI PERBEDAAN GENDER - Ernadya Regita Cahyani; Martini Martini; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aims to analyze the creative thinking skills of junior high school students on environmental pollution material in terms of gender differences. This type of research is descriptive research with a quantitative approach. The research subjects were class VII B students of SMP Negeri 1 Paciran for the academic year 2020/2021 with a sample of 30 students. The sample was determined by purposive sampling. Data collection techniques using tests and questionnaires. The data analysis technique used descriptive statistical processing. The results showed that the percentage score of students' creative thinking skills on indicators of fluency was 87.6%, original thinking was 52%, flexible thinking was 68.5%, and elaboration was 67%. Based on the analysis of gender differences. the ability of male students on the fluency indicator was 87.14%; originality 53.57%; flexibility 63.52%; elaboration 70%. The ability of female students on the fluency indicator is 88.13%; originality 50.63%; flexibility 72.81%; elaboration 64.38%. In terms of gender differences, the indicators of fluency and flexibility of female students are higher than male students. Originality and elaboration indicators of male students are higher than female students. Positive responses through questionnaires showed that male students had higher creative thinking skills than female students.